2021
DOI: 10.1002/mnfr.202100111
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Protects Against Diet‐Induced Body Weight Gain, Increases Energy Expenditure, and Induces White Adipose Tissue Beiging

Abstract: Scope Interventions that boost NAD+ availability are of potential therapeutic interest for obesity treatment. The potential of nicotinamide (NAM), the amide form of vitamin B3 and a physiological precursor of nicotinamide adenine dinucleotide (NAD)+, in preventing weight gain has not previously been studied in vivo. Other NAD+ precursors have been shown to decrease weight gain; however, their impact on adipose tissue is not addressed. Methods and results Two doses of NAM (high dose: 1% and low dose: 0.25%) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…Nicotinamide is generally known to decrease cytokine production and inflammatory responses in various cell types and tissues ( Mendez-Lara et al., 2021 ; Rehman et al., 2021 ; Ungerstedt et al., 2003 ; Zheng et al., 2019 ); however, the mechanism by which NAM alters adaptive T cell immunity is unknown but is crucial to understand because this is a widely used human supplement. For example, it is unclear if NAM specifically affects naive T cell transition into effector T cells, effector function itself, or subsequent responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotinamide is generally known to decrease cytokine production and inflammatory responses in various cell types and tissues ( Mendez-Lara et al., 2021 ; Rehman et al., 2021 ; Ungerstedt et al., 2003 ; Zheng et al., 2019 ); however, the mechanism by which NAM alters adaptive T cell immunity is unknown but is crucial to understand because this is a widely used human supplement. For example, it is unclear if NAM specifically affects naive T cell transition into effector T cells, effector function itself, or subsequent responses.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies demonstrated that NAM mediates chemopreventive effects by boosting immune cell cytokine production in different models of murine cancers ( Buque et al., 2020 ; Scatozza et al., 2020 ). Conversely, other studies showed that NAM supplementation reduced inflammation protecting against high fat diet-induced inflammation ( Mendez-Lara et al., 2021 ; Mitchell et al., 2018 ), an Experimental Autoimmune Encephalitis (EAE) model ( Kaneko et al., 2006 ), and pulmonary injury caused by ischemia/reperfusion in rats ( Su et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ fibrosis is characterized by excess deposition of extracellular matrix proteins. Administration of NA, NAM, and NR attenuates experimental liver fibrosis [ 14 , 121 , 122 , 123 , 124 ], potentially indicating that an insufficient NAD+ supply may underlie organ fibrosis. Similar favorable effects could be conceivably suggested for NAD+-increasing interventions aiming to directly combat myocardial fibrosis.…”
Section: In Vitro Cardioprotective Effects Of Nad+ Sourcesmentioning
confidence: 99%
“…Accordingly, many studies have revealed that dietary administration of NAD+ precursors, such as tryptophan, nicotinic acid (NA, also termed niacin), nicotinamide (NAM), and nicotinamide riboside (NR), and its phosphorylated form, nicotinamide mononucleotide (NMN), efficiently raises the tissue NAD+ content in rodents and humans [ 8 , 9 ]. In particular, NAM, NMN, and NR administration has been reported to prevent obesity and improve glucose tolerance in mice [ 10 , 11 , 12 , 13 , 14 ] and favorably influenced fatty liver by reducing oxidative stress and inflammation in aged, diet-induced obese mice [ 15 ]. Conceivably, NAD+ precursors may protect the cardiovascular system [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%